Preliminary Observation of Problem-Based Learning to Improve Elementary Students' Mathematical Problem-Solving Skills - Isriani, Weni Putri; Safitri, Ulandari (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This activity aimed to examine the mathematical problem-solving abilities of elementary school students. The low level of problem-solving skills must be a key focus when designing instructional materials. High-quality learning tools can help students develop strong problem-solving skills. This study employs a descriptive research design using a qualitative approach. The initial observation in this study aims to enhance students' problem-solving abilities, particularly in mathematics, by investigating the teaching materials currently used and developed by teachers, and whether these materials require further development. This includes whether there is a need to develop problem-based learning (PBL) materials grounded in real-life situations to improve students' mathematical problem-solving skills. Initial observations at SDN 03 Bunga Tanjung and SDN 04 Kajai reveal the following: (1) The learning process is still predominantly teacher-centered, (2) Only a small number of students are actively involved in the learning process, with many appearing distracted or playing with peers, (3) During lessons, teachers are not using student worksheets that match the students' characteristics; instead, they rely solely on standard textbooks. Based on these findings, further research is needed to develop problem-based learning materials for elementary school students.